Effect of disease activity on the clinical outcome of SARS CoV-2 in patients with underlying rheumatic diseases; data from global rheumatology alliance - Perveen, Shahida; Samreen, Saba; Gul, Haris; Salim, Babur; Nasim, Amjad (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the effect of disease activity on clinical outcomes of coronavirus disease-2019 in patients with rheumatic diseases. Method: The prospective, cohort study was conducted from January 1st to June 30th, 2021, at Rheumatology department, Fauji Foundation Hospital, Rawalpindi. It comprised patients of rheumatic disorders who were affected by coronavirus disease-2019. The patients were categorised according to rheumatic disease activity into remission group I, low disease activity group II, moderate group III and high–activity group IV. Coronavirus disease-2019 outcomes compared included recovered vs death, hospitalisation yes vs no, mechanical ventilation yes vs no. The association of disease activity status with coronavirus disease-2019 outcomes was explored. Data was analysed using SPSS 23. Results: Of the 100 patients, 78(78%) were females and 22(22%) were males. The overall mean age was 45.60±13.7 years. There were 23(23%) patients in group I, 42(42%) patients in group II, 21(21%) patients in group III and 14(14%) patients in group IV. Overall,17(17%) patients died and 83(83%) patients survived. In group III, 7(33.3%) patients died, followed by 6(42.9%) in group IV (p<0.05). In total, 7(7%) patients needed mechanical ventilation, with 3(21.4%) being in group IV (p<0.05). Hospitalisation was needed in 33(33%) cases, and intergroup comparison was non-significant (p>0.05). Conclusion: Patients with severe rheumatic autoimmune disease affected by coronavirus disease-2019were more likely to die and require invasive ventilation. Key Words: Arthritis, Connective tissue diseases, Rheumatoid arthritis, Ankylosing spondylitis, Scleroderma, Vasculitis.